Implementasi Model “Pasti Aksi Pasti Literasi” Dalam Pengembangan Life Skill Siswa: (Studi Kasus di Madrasah Tsanawiyah Unggulan Darul Falah Jerukmacan Mojokerto) - Muhammad Assyauqii Zam Zami; Rofiatul Hosna (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
This study aims to analyze the implementation of the “Pasti Aksi Pasti Literasi” learning model in developing students’ life skills at MTs Unggulan Darul Falah Jerukmacan Mojokerto. The research employed a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation. Data analysis using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that the “Pasti Aksi Pasti Literasi” learning model was able to increase students’ active participation through the integration of literacy activities, real actions, and value reflections in the learning process. The implementation of this model positively contributed to the development of students’ personal skills, social skills, academic skills, and spiritual skills. In addition, literacy- and action-based learning created a more contextual, collaborative, and meaningful learning atmosphere. Supporting factors included teacher competence, school literacy culture, and adequate learning facilities, while inhibiting factors included limited learning time and differences in students’ literacy abilities. This study indicates that the “Pasti Aksi Pasti Literasi” model is relevant as an innovative learning model in Islamic Religious Education to address the challenges of 21st-century education.